MENINGKATKAN KEMAPUAN MENULIS GURU MELALUI PELATIHAN PENELITIAN TINDAKAN KELAS (PTK) - Ahmad, Ahmad; Ratu Perwira Negara, Habib; Irfan, Pahrul; Hammad, Rifqi; Abd. Latif, Kurniadin; Zulfikri, Muhammad; Arfa, Muhammad (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2023)
The purpose of this service is to improve teachers' writing skills through the application of Classroom Action Research Training (PTK). This activity is in collaboration with the West Lombok School Principals Group (MKKS) and the Basic Education Quality Improvement Agency (BPMPD) (CLUSTER VI Lingsar District). The training organized involves a series of structured activities designed to improve teacher skills in Compiling and creating research reports Classroom actions which are further amended in the form of research articles. By involving teachers as agents of change, this dedication has succeeded in creating a dynamic and responsive learning environment. In addition, teachers have developed skills of analysis, reflection, and adjustment of their learning practices. Thus, the conclusion of this service confirms that the teachers who participated in the PTK training have been able to understand all the material presented and create a positive impact to develop themselves in the learning process that is inseparable from the implementation of classroom action research (PTK) in the classroom.